Letter : Assistance to Republican Spaniards - Picken, M.
038-0001-001 Mr. Bell NATIONAL JOINT COMMITTEE FOR SPANISH RELIEF AND BASQUE CHILDREN'S TRUST LTD. PRESIDENT: THE DUCHESS OF ATHOLL, D.B.E., D.C.L. CHAIRMAN: THE LADY LAYTON VICE-CHAIRMAN: THE EARL OF LISTOWEL. HON. TREASURER: VISCOUNT CECIL OF CHELWOOD, P.C. K.C. HON. SECRETARIES: Mr. D.R. GRENFELL, M.P. Mr. WILFRID ROBERTS, M.P. HON. APPEAL SECRETARY: Mrs. V.E. MILLER MOORE, M.B.E. SECRETARY: MISS M. PICKEN. 39, VICTORIA STREET, LONDON, S.W.1. TELEPHONE: ABBEY 7463 3rd October 1949. Dear Mr. Tewson, Assistance to Republican Spaniards. In Lady Layton's absence I acknowledge your letter of September 30th with reference to the above subject. Your letter will be put before her on her return from Czecho-Slovakia about the beginning of November. Yours faithfully, M Picken Secretary. Vinvent Tewson Esq., C.B.E., M.C., Transport House, Smith Square, S.W.1. 292/946/38/1